Recreational MDMA use in Norway: results from an internet convenience sample - Grønnerød, Cato; Rønningen, Thea; Haugsjå, Ingrid Rike; Andersen, Kristoffer A. A.; Lindvall Dahlgren, Camilla; Kvam, Tor-Morten (Frontiers in Psychiatry, 2025)
The purpose of the articleIn recent years, a renewed interest has emerged in investigating the use of MDMA in the treatment of mental disorders. However, knowledge about the characteristics of recreational use of MDMA, its contexts and effects are limited.MethodsWe recruited adult Norwegian participants aged 18 to 65 who reported having had a memorable experience after using MDMA. They completed an anonymous internet survey with 150 items covering matters related to recreational use of MDMA, as well as four standardized measures related to their experience and to personality functioning. We present descriptive statistics (frequencies, means, and standard deviations) from the survey.ResultsWe recruited 654 participants, 608 of which were eligible for inclusion in the data analysis (60.5% male; 89% 45 years or younger). Participants reported recreational (65.5%) and therapeutic (22.9%) motivation for MDMA use, mostly at home (28.3%) or at somebody else’s home (34.4%). Participants were well prepared (63%) and most had a clear intention behind their use (54.3%). They were clearly in favor of using MDMA therapeutically (84.7%). Mental distress or disorders were frequently reported (82.1%), but also a large degree of improvement, especially for internalizing disorders such as PTSD, social anxiety and depression. Persistent negative effects were relatively rare and short lived.ConclusionsOur sample reported positive experiences and effects of recreational MDMA use, with a small minority reporting problematic effects and negative experiences. Self-perceived symptoms were reported as improved, especially for internalizing disorders. Participants reported positive changes in many aspects of life.